دانانی بەرنامەیەکی ڕاهێنانی پێشنیارکراو بۆ گەشەپێدانی لێهاتووییەکانی ڕێکخستنی پێشانگای هونەری (curating) لای خوێندکارانی کۆلێجی هونەر (توێژینەوەی هەڵێنجراو) - خالد, پ.ی.د. حسن فخرالدین; ڕشید, پ.د. ڕێبوار سعید; امین, یادگار محمد (Sulaimani Journal for Humanities, 2023)
This research attempts to create a practical program as a proposition that contributes to the capability of curating exhibitions, especially for students from the college of fine arts/ visual art department. The research consists of four parts, the first is the (general framework), here the research problem is the absence of the subject of the curating art exhibition. Moreover, the main aim of the research is to create a practical program for the art curating. The second part is the (theoretical framework and previous researches), this is divided into two parts which are the practical program and the concept of curating, furthermore, the comparison among previous researches. The third one is the (research methodology), to make this practical program, the descriptive and analytical method is considered. the sample of the research also concentrates on undergraduate students from stages three and four – college of fine arts/ visual art department (2022-2023). In order to work with the fact and get the validity of data, (Research Survey) is used in collecting and analyzing information achieved from the response of the experts. Finally, the last part is dedicated to the (conclusion).
Keywords: بەرنامەی ڕاهێنانی کیوڕەیتینگ